POLITENESS MAXIMS USED BY THE HOST OF “BUKAN EMPAT MATA” TALK SHOW IN THE COMMENTATOR EPISODE - WARDHANA, RANDY AGUS SETYA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: politeness maxims, violation of politeness maxims, talk show, Bukan Empat Mata Communication is essential for life. In conducting a communication, people are always required to express a politeness. But people sometimes do violation of politeness.It usually happens in entertainment. In this study, the researcher conducted a research about politeness maxim used by Tukul Arwana in Bukan Empat Mata that was broadcast September, 25th 2013. There are two problems to be solved, namely: (1) what politeness maxims are used by the host of Bukan Empat Mata in “TheCommentator” episode, and (2) what kind of politeness maxims are violated bythe host of Bukan Empat Mata in “The Commentator” episode. This research used qualitative approach because the analysis is in the form of  description rather than number. The research was conducted through documentary analysis since the researcher analyzed Tukul Arwana’s utterances in his transcript dialogue containing politeness maxim and violation of politeness maxim. The result of the research showed that the host applied five politeness maxims, namely tact maxim (5), approbation maxim (15), modesty maxim (1), aggrement maxim (10), and sympathy maxim (1). On the other hand, he also applied three violation of politeness maxim, namely violation of generosity maxim (1), violation of approbation maxim (11), and violation of modesty maxim (1). Based on the result of the study, the researcher wants to give suggestions for the next researchers who are interested in the same field to find more sources of the theory to enrich the comprehension about politeness maxim and violation of politeness maxim. The next suggestion for further researchers is the coverage canbe more expanded and better as unit analysis in order to have an extra comprehensive research in analyzing the data that was found in politeness principle.